Radiographic Predictors of DRUJ Instability with Distal Radius Fractures - Omokawa, Shohei; Iida, Akio; Fujitani, Ryotaro; Onishi, Tadanobu; Tanaka, Yasuhito (Journal of Wrist Surgery, 2014)
Because the distal radioulnar joint (DRUJ) is an inherently unstable joint, the diagnosis and treatment of DRUJ instability is often difficult in a clinical hand surgery practice. Several soft tissue stabilizers are recognized, of which the deep limbs of the radioulnar ligament are primary stabilizers. This article discusses the predictors of DRUJ instability in distal radius fractures based on our clinical and biomechanical analyses.
Keywords: radioulnar; joint; instability; predictor